Basin‐scale Green's functions from the ambient seismic field recorded by MeSO‐net stations. Issue 4 (9th April 2016) - Viens, Loïc; Koketsu, Kazuki; Miyake, Hiroe; Sakai, Shin'ichi; Nakagawa, Shigeki
Abstract: Seismic waves propagating through the Earth can be significantly affected by velocity structures such as sedimentary basins. We investigate the propagation characteristics of seismic waves across the Kanto basin, Japan, using Green's functions extracted from the ambient seismic field. We use two stations situated on the eastern and southern edges of the basin as virtual sources, and approximately 420 stations, which are mainly a part of the Metropolitan Seismic Observation network (MeSO‐net), as receivers. Using seismometers aligned along two straight lines with the virtual sources, we find that several types of waves can be recovered, each with different sensitivities to the layers that compose the basin. We also show that after amplitude calibration, the extracted Green's functions can accurately simulate the seismic waves of two moderate M w 4–5 shallow earthquakes that occurred close to the virtual sources. Furthermore, we find that the distribution of the 5% damped pseudovelocity response at a period of 6 s computed from the records of each event and the Green's function waveforms have similar amplification patterns. This study supports the fact that dense networks recording continuously the ambient seismic field in metropolitan areas can be used to accurately assess seismic hazard at high spatial resolution. Key Points: Basin‐scale Green's functions recovered from the ambient seismic field recorded by MeSO‐net stations Clear sensitivity of extracted seismic waves to the multilayered Kanto basin Large potential of dense seismic networks like MeSO‐net to improve high‐resolution shake maps